Elaboration and characterization of composite clays based on "Coal waste-Olive pomace" mixtures. (2022) - Harrami, M.; El Fami, N.; Moussadik, A.; Khachani, N.; Taibi, M.; Diouri, A.
Abstract: The problem of pollution at the local level has always been a challenge for developing countries. Effluents from olive oil industry in rural areas cause soil contamination by poly-phenolic fats, causing asphyxiation of the terrestrial ecosystem. Moreover, mining waste, such as coal gangue, represents also the risk of acids and toxic elements, such as heavy metals and sulphates, infiltrating into water table. The purpose of this study is to characterize the materials used in a composite clay based on "Coal waste-Olive pomace" (CW-OP) mixtures. Different grain size fractions are studied separately and analyzed by X-ray fluorescence, X-ray diffraction and Infrared spectroscopy. These analyzes showed that the studied waste, contain essentially a mineral part formed by silica and various clays, as well as coal's residues. These minerals are generally found in building materials.